Efforts to Improve Descriptive Writing Skills Using Magic Card Media for Ninth Grade Students in Junior High School - Elang Latu Lanang; Trinil Dwi Turistiani; Eka Lidia Ustanti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Descriptive writing skills are essential competencies that students at the junior high school level must possess, especially to develop critical thinking skills and language abilities. Descriptive texts provide students with the opportunity to describe objects, places, or situations in detail, which in turn trains students in organizing ideas and enriching vocabulary. However, challenges in teaching these skills are still frequently encountered in the field. This study aims to improve descriptive writing skills among ninth-grade junior high school students through the use of Magic Card media. The research employs a Classroom Action Research (CAR) method conducted in two cycles. Each cycle includes stages of planning, implementation, observation, and reflection. Data were collected through observations, interviews, and writing tests conducted at the end of each cycle. The results show that the application of Magic Card media can significantly enhance students' descriptive writing skills. In Cycle 1, the average student score was only 65, with issues such as limited vocabulary, difficulty in organizing ideas, and lack of creativity. After reflection and adjustments in Cycle 2, which included providing more detailed guidance, staged practice, and individual work, the average student score increased to 75. This improvement was evident in the increased use of varied vocabulary, more logical organization of ideas, and creativity in writing descriptive texts. Thus, Magic Card media proves to be effective in improving descriptive writing skills among ninth-grade junior high school students. This study suggests that teachers should utilize creative and interactive learning media, such as Magic Cards, to help students develop their writing skills optimally.